Manajemen Kurikulum Tahfidz Al-Qur’an di Kuttab Al Faruq Sukoharjo - Chusniyah, Atin; Makruf, Imam (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
The curriculum management of tahfidz Al-Qur'an is one of the important factors in the success of tahfidz learning. This study aims to examine the curriculum management of tahfidz Al-Qur'an in Kuttab Al Faruq Sukoharjo, as well as the supporting and inhibiting factors. This research uses a qualitative approach with a case study method. Data were collected through interviews, observation, and documentation. The results showed that the management of the Qur'an tahfidz curriculum at Kuttab Al Faruq Sukoharjo has been carried out well. Careful planning, structured implementation, and diverse evaluations create a strong framework to achieve tahfidz learning goals. Supporting factors for the management of the Qur'an tahfidz curriculum are the support of the head of Kuttab, the adequate competence of tahfidz teachers, the support of the parents of students, and the learning climate that is conducive to memorization. The inhibiting factors for the management of the Qur'an tahfidz curriculum are the large number of students, the diverse abilities of students, the lack of motivation of students to memorize, and the lack of parental cooperation in monitoring students' memorization. The urgency of this research lies in an in-depth understanding of tahfidz curriculum management along with supporting and inhibiting factors in the context of Kuttab Al Faruq Sukoharjo. The contribution of the research lies in recommendations that can help improve the effectiveness of tahfidz curriculum management in similar institutions.